An Energy Approach to Determine the Martensite Morphology in Nanocrystalline NiTi1 . Issue 4 (31st January 2017) - Petersmann, Manuel; Pranger, Wolfgang; Waitz, Thomas; Antretter, Thomas
Abstract : The characteristic features of martensite in nanocrystalline Ni‐50 at %Ti are a compromise between interface and strain energies introduced into the material when a grain transforms from austenite to a finely laminated martensite structure. This paper focuses on the evaluation of these energies. Whereas for grain sizes <100 nm a single laminate is frequently observed, in larger grains the higher strain energy of this structure leads to hierarchical twinning. As the predominant contribution the strain energy is computed by the finite element method. Interface energies at the twin‐ as well as the grain‐boundaries are subsequently added. Suitable scaling relations yield the evolution of twin spacing and predict that multiple laminates become favorable at a diameter range of 70–90 nm. Abstract : Nanocrystalline NiTi has become increasingly attractive as an advanced shape memory material, well‐known for its biomedical applications . This work determines the energies involved in the martensitic phase transformation of this intermetallic alloy taking advantage of the results provided by HRTEM experiments. Numerical simulations explain the martensite morphology depending on the grain size.